2008
DOI: 10.2167/cit345.0
|View full text |Cite
|
Sign up to set email alerts
|

Managing Wildlife-based Tourism: Edging Slowly Towards Sustainability?

Abstract: It is increasingly acknowledged that cetacean-based tourism may not be as low in impact as many hope or presume, and that any long term and systematic human interactions with populations of wild animals need to be rigorously monitored and carefully managed. This paper reviews a series of recent developments in the management of tourist interactions with dolphins at Shark Bay (Western Australia). We argue that collectively these developments represent a paradigmatic shift in the way commercial tourism encounter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Drawing on decades of detailed behavioral observations, this study showed a significant decline in dolphin abundance associated with vessel-based dolphin watching tourism involving only two tour operators. Discovery of this impact triggered government intervention leading to the revocation of one of the marine mammal watching tourism permits (Higham & Bejder, 2008).…”
Section: Use Levels and Impactsmentioning
confidence: 99%
“…Drawing on decades of detailed behavioral observations, this study showed a significant decline in dolphin abundance associated with vessel-based dolphin watching tourism involving only two tour operators. Discovery of this impact triggered government intervention leading to the revocation of one of the marine mammal watching tourism permits (Higham & Bejder, 2008).…”
Section: Use Levels and Impactsmentioning
confidence: 99%
“…As a consequence the number of operators was reduced to half by the Western Australian Government. Higham and Bejder (2008) contend that this was a milestone event in the management of wildlife tourism since it was a move from simple acceptance of the Precautionary Principle towards objective science. It also provides an excellent example of the progression towards LAC III in the Duffus Dearden model and the kinds of management interventions required at this point.…”
Section: Discovered That Duffus Andmentioning
confidence: 99%
“…The last estimate was that whale watching attracts approximately 13 million people in 119 different countries generating US$ 2.1 billion (O'Connor, Campbell, Cortez, & Knowles, 2009). Managers charged with ensuring the protection of cetaceans are concerned about both the short-term and long-term effects of these interactions, and are seeking to implement regulatory schemes (Higham & Bejder, 2008;Higham et al, 2009). The swim-with dolphin programs rely primarily on free-ranging spinner dolphins and their predictable daily behavior.…”
Section: Introductionmentioning
confidence: 99%